1999
DOI: 10.1097/00005344-199901000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and Hormonal Responses to Nicorandil in a Canine Model of Acute Ischemic Heart Failure: A Comparison with Cromakalim and Nitroglycerin

Abstract: The pharmacologic profiles of nicorandil in the cardiovascular system have been characterized by K-channel opening and nitrate activities. However, the effects of nicorandil on acute heart failure have yet to be elucidated. To investigate the effects of nicorandil under such pathophysiologic conditions, we administered nicorandil intravenously to dogs with acute ischemic heart failure induced by coronary embolization and compared the results with those induced by cromakalim and nitroglycerin. The heart failure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…In the acute ischemic heart failure canine model, nicorandil at similar concentrations to the present ones increased cardiac output and SV mediated by the drug's K-channel opening activities and by the reduction of venous tone by its nitrate properties [6]. Furthermore, in the canine acute congestive heart failure model, nicorandil may exert beneficial hemodynamic effects mainly due to decrease in both afterload and preload rather than the coronary vasodilator effect [7].…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…In the acute ischemic heart failure canine model, nicorandil at similar concentrations to the present ones increased cardiac output and SV mediated by the drug's K-channel opening activities and by the reduction of venous tone by its nitrate properties [6]. Furthermore, in the canine acute congestive heart failure model, nicorandil may exert beneficial hemodynamic effects mainly due to decrease in both afterload and preload rather than the coronary vasodilator effect [7].…”
Section: Discussionsupporting
confidence: 51%
“…The increase in EDV induced by nicorandil is not likely due to venous contractions, because nicorandil dilates capacitance vessels, as does nitroglycerin, but does not contract capacitance vessels [6]. Neither elongation of relaxation time nor the enhancement of lusitropy in the left ventricle seems likely to increase EDV, because the left ventricular end-diastolic pressure-volume curve at the filling phase was not affected by nicorandil (our observation).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…3 Acute administration of nicorandil has indeed been shown to be effective in the treatment of heart failure, predominantly as a result of its vasodilator effects. 4,5 A single oral dose of nicorandil increased coronary blood flow and ameliorated exercise-induced LV dysfunction in patients with previous myocardial infarction. 6 Intravenous administration of nicorandil also attenuated exercise-induced LV diastolic dysfunction in individuals with hypertrophic cardiomyopathy, probably as a result of its beneficial effect on abnormal coronary microcirculation.…”
mentioning
confidence: 99%
“…By virtue of the well-balanced decrease in both preload and afterload it induces, nicorandil improves the hemodynamics of patients with AHFS. 7, 16 It is recommended that intravenous nicorandil therapy be initiated with a bolus injection to ensure prompt improvement of hemodynamics. Although prompt improvement of hemodynamics should improve the prognosis of patients with AHFS, 4 it has been reported that treatment with the natriuretic peptide analog, nesiritide, may cause deterioration of renal function and thus the prognosis of patients with decompensated HF, possibly via induction of hypotension by bolus administration or continuous infusion of a high dose.…”
Section: Discussionmentioning
confidence: 99%